Case report: disseminated Staphylococcus aureus infections in two infant desert cottontail rabbits (Sylvilagus audubonii) - Paul, Gabriele C.; Friend, Daniel G. (Wildlife Rehabilitation Bulletin, 2024)
<em style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Staphylococcus aureus<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> is a frequent pathogen in mammals, including rabbits. It can cause suppurative inflammation with a variety of clinical presentations, sometimes resulting in high morbidity and mortality. Outbreaks have been reported in both domestic European rabbits (<em style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Oryctolagus cuniculus<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">), and in cottontail rabbits (<em style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Sylvilagus<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> spp.). The Colorado Wild Rabbit Foundation recently identified two cases of disseminated <em style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">S. aureus<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> infections in sibling infant desert cottontail rabbits (<em style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">S. audubonii<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">) that were presented for rehabilitation. This case report describes the course of the disease, attempted treatment, and pathology findings. Culture and sensitivity tests indicated susceptibility of the pathogen to all antibiotics tested, including trimethoprim-sulfamethoxazole (TMP-SMZ). However, both cases resulted in disseminated spread, against which TMP-SMZ was ineffective. Cottontail rabbit rehabilitators should be aware of the potentially subtle clinical signs, the possibility of outbreaks within a facility, and the difficulties in treating this disease.